Food Insecurity in the Households of Polish Elderly: Diversity in the Perception of Its Causes by Demographic and Socioeconomic Characteristics - Robert Gajda; Marzena Jeżewska-Zychowicz; Marzena Styczyńska; Małgorzata Agnieszka Jarossová (Foods, 2022)
The aging of societies and the quality of life of the elderly may be accompanied by food insecurity. The aim of the study was to find the relationships between the perceptions of various causes of food insecurity, i.e., financial, social, health, and spatial, and then between those and the selected sociodemographic characteristics. The survey was conducted in late 2018 and early 2019 among 760 people aged 65 and older in two regions of Poland. Factor analysis with the use of principal component analysis (PCA) was used to identify the main causes of the prevalence of food insecurity. Cluster analysis using Ward’s hierarchical classification and logistic regression analysis were used to assess the relationship between the identified reasons for food insecurity, demographic characteristics, and socioeconomic status (SES). Two groups of causes that favor the experience of food insecurity among the elderly were identified, i.e., economic–social reasons and spatial–health reasons. They relate to such situations of food insecurity as concerns about food shortages, lack of staple foods, limited size or frequency of meals, and skipping meals. The high importance of economic–social (HE-S) reasons was associated with the low importance of spatial–health (LS-H) reasons, and conversely, the high importance of spatial–health (HS-H) causes was associated with the low importance of economic–social (LE-S) causes. HE-S and LS-H reasons were combined with low SES and residence in a city of more than 100,000 inhabitants. HS-H causes, on the other hand, were associated with LE-S causes and living in rural areas or towns of fewer than 100,000 inhabitants, as well as high SES. This specificity should be considered in the development of strategies and interventions aimed at reducing the phenomenon of experiencing food insecurity in the elderly population.